Hölder Continuity of the Saddle Point Set for Real-Valued Functions. (2nd November 2017) - Li, Xiao-Bing; Lin, Zhi; Wang, Qi-Lin; Chen, Jia-Wei
ABSTRACT: This paper is concerned with Hölder continuity of the solution to a saddle point problem. Some new suﬃcient conditions for the uniqueness and Hölder continuity of the solution for a perturbed saddle point problem are established. Applications of the result on Hölder continuity of the solution for perturbed constrained optimization problems are presented under mild conditions. Examples are given to illustrate the obtained results.